2011
DOI: 10.1007/s12033-011-9431-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of Classical Swine Fever Virus Envelope Glycoprotein E2 as Recombinant Polyhedra in Baculovirus-Infected Silkworm Larvae

Abstract: Although, classical swine fever virus (CSFV) envelope glycoprotein E2 subunit vaccine has been developed using the baculovirus expression system, the expression of viral antigens in baculovirus-infected insect cells is often ineffective. Therefore, an alternative strategy to the traditional baculovirus expression system is needed that is more productive and effective. Here, we report a novel strategy for the large-scale production of a CSFV E2 in the larvae of a baculovirus-infected silkworm, Bombyx mori. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…The results indicated that immunization with a chimeric protein induced a significant serum antibody reaction against Polyhedrin and the coat protein. This demonstrated that both were immunogenic and that the baculovirus protein perhaps increases the immune response as previously observed [17,22] for another baculovirus carrier protein and the Polyhedrin. Similar methods have already been developed and employed to purify target proteins [16-18]; however, the novelty presented here is the expression of a full-length protein in fusion with the Polyhedrin and the use of complete cadavers of caterpillars as bioreactors.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The results indicated that immunization with a chimeric protein induced a significant serum antibody reaction against Polyhedrin and the coat protein. This demonstrated that both were immunogenic and that the baculovirus protein perhaps increases the immune response as previously observed [17,22] for another baculovirus carrier protein and the Polyhedrin. Similar methods have already been developed and employed to purify target proteins [16-18]; however, the novelty presented here is the expression of a full-length protein in fusion with the Polyhedrin and the use of complete cadavers of caterpillars as bioreactors.…”
Section: Discussionsupporting
confidence: 77%
“…This feature avoided the polyhedral matrix formation and the nuclear localization by the chimeric protein. Previous research has used, besides the polh gene fused with a gene of interest, a second polh gene copy [14,17]. Although the presence of a second copy of polh could improve the chimeric crystal formation and nuclear localization, we observed that the presence of only one fused Polyhedrin-copy was sufficient to form a crystal structure.…”
Section: Discussionmentioning
confidence: 59%
“…Classical swine fever virus envelope glycoprotein, E2, fused with polyhedron from baculovirus has been expressed in silkworm larvae and E2 has been purified by solubilization of recombinant polyhedra. Virus-neutralizing activity is induced when purified E2 is used to immunize mice [77]. In this case, virus-neutralizing activity is induced after immunization with recombinant polyhedra.…”
Section: Vlps Production Using Silkworm Larvae and Their Applicationsmentioning
confidence: 99%
“…Meanwhile, recent findings have shown powerful immunogenicity among baculovirus expressing E2 glycoprotein (Dong and Chen 2007), thus, further proving for quick and economical production of vaccines in veterinary industry (Wu et al 2010). Later, Lee et al 2012 achieved production of recombinant E2 glycoprotein using BVES system in silkworm larvae (Lee et al 2012).…”
Section: Introductionmentioning
confidence: 99%